2015
DOI: 10.1002/tox.22118
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic evaluation of functionalized single-walled carbon nanotube in mice bone marrow cells

Abstract: With their unique structure and physico-chemical properties, single walled carbon nanotubes (SWCNTs) have many potential new applications in medicine and industry. However, there is lack of detailed information concerning their impact on human health and the environment. The aim of this study was to assess the effects, after intra peritoneal injection of functionalized SWCNTs (f-SWCNT) on the induction of reactive oxygen species (ROS), frequency of structural chromosomal aberrations (SCA), frequency of micronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Furthermore, SWCNT fluoresce in a unique nIR window (1000 to 1300 nm), which reduces photon scattering and enhances imaging penetration depths, enabling throughcranium (43) and in vivo imaging (38). This optical window could enable the through-cranium fluorescence imaging of cortical 5-HT neuromodulation without a cranial window for chronic 5-HT imaging in animal models, although it is necessary to note that probe delivery may require cranial surgeries or injections similar to the status quo for delivery of adeno-associated viruses (43,44). Furthermore, previous work has demonstrated that SWCNT-based neuromodulator probes are tractable for use in nonmodel species (26), further expanding the repertoire of neurological studies to be undertaken with nIRHT and other probes of its class.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SWCNT fluoresce in a unique nIR window (1000 to 1300 nm), which reduces photon scattering and enhances imaging penetration depths, enabling throughcranium (43) and in vivo imaging (38). This optical window could enable the through-cranium fluorescence imaging of cortical 5-HT neuromodulation without a cranial window for chronic 5-HT imaging in animal models, although it is necessary to note that probe delivery may require cranial surgeries or injections similar to the status quo for delivery of adeno-associated viruses (43,44). Furthermore, previous work has demonstrated that SWCNT-based neuromodulator probes are tractable for use in nonmodel species (26), further expanding the repertoire of neurological studies to be undertaken with nIRHT and other probes of its class.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study demonstrated that SWCNTs and DWCNTs significantly reduced the number of CFU and decreased the migration of EPCs in response to vascular endothelial growth factor (VEGF) in ApoE −/− mice. Moreover, Patlolla et al [ 40 ] recently demonstrated the induction of oxidative stress mediated genotoxicity in bone marrow collected from the mice exposed to SWCNTs. Considered together, these results suggest that CNTs impair EPC functional activities.…”
Section: Discussionmentioning
confidence: 99%
“…These results were published by Patlolla et al . in 2010 [ 83 ] and 2016 [ 84 ], who investigated the effects of MWCNTs and then SWCNTs on adult male Swiss-Webster mice via intraperitoneal exposures of 0.25, 0.5 and 0.75 mg/kg. The MN data from these studies reveal only the top two doses could induce significant chromosomal breakage, which was further supported in both cases by positive comet data and CAs [ 83 , 84 ].…”
Section: Literature Quality Evaluation Resultsmentioning
confidence: 99%